Four new species and five new distribution records of the jumping spider genus Stenaelurillus Simon, 1886 (Salticidae: Aelurillines) from India - Tripathi, Rishikesh; Kuni, Nikhil; Kadam, Gautam; Kumaran, Keerthana P.; Sudhikumar, Ambalaparambil Vasu (European Journal of Taxonomy, 2024)
Four new species of the jumping spider genus Stenaelurillus Simon, 1886 are described from India: Stenaelurillus feral Tripathi, Kuni & Kadam sp. nov. (♂, from the Eastern Coastline), S. naldurg Kuni, Kadam & Tripathi sp. nov. (♂♀, from the Deccan Plateau), S. judithbleisterae Kadam, Tripathi & Kuni sp. nov. (♂♀, from the Western Ghats) and S. solapur Kuni, Tripathi & Kadam sp. nov. (♂♀, from the Deccan Plateau). Detailed diagnoses, descriptions, illustrations, natural history and distribution map are provided. Additionally, new locality records for the other five species within the states are presented and mapped.